Simultaneous Laparoscopic Surgery for Bladder Diverticulum and Urachal Remnant: A Case Report - Masaki Murata; Kohei Inui; Moto Hasegawa; Yohei Ikeda; Yuki Nakagawa; Noboru Hara; Tsutomu Nishiyama (Case Reports in Urology)
A 44-year-old woman visited a hospital with microscopic hematuria in June 2009. Computed tomography showed a large bladder diverticulum at right lateral wall and urachal remnant. Cystoscopic examination showed a large diverticulum at the right lateral wall that closes to the dome. She was followed up closely without therapeutic intervention; however, the residual urine increased gradually and frequent bladder diverticulitis developed. She underwent laparoscopic bladder diverticulectomy and excision of the urachal remnant simultaneously without any complications in August 2017. Laparoscopic approach for a large bladder diverticulum and urachal remnant is useful with safe, effective, and minimally invasive.